Resistance Materials. Female Antagonism in the No-TAV Case - D’Ascenzio, Anna (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Anna D’Ascenzio Title (English): Resistance Materials. Female Antagonism in the No-TAV Case Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 155-161 Page Count: 7 Citation (English): Anna D’Ascenzio, “Resistance Materials. Female Antagonism in the No-TAV Case,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 155-161.